The construction of Chineseness in the Chinatowns of the Hague and Amsterdam. - Yuyao Mei; Ilse van Liempt (European Journal of Geography)
Since the late 1990s, the symbolic economy was coined to describe the economy based on cultural production and consumption. Chinatowns are a typical representation of this new consumption-based economy in which symbols play an important role. The existence of a Chinatown has helped metropolises to label themselves as global and diverse cities but Chinatowns do not always meet the gazers’ expectations on its cultural and aesthetic features. Moreover, they rework the concept of Chineseness to achieve the goal of city officials’ ideas of an ‘ideal’ Chinatown. This article deconstructs the intangible and ambiguous aspects around the concept of Chineseness through a geosemiotic lens. By analysing the linguistic landscape and paying additional attention to socio-spatial interactions around signs, this research makes a contribution to the field of Chinatown studies. Moreover, as a comparative empirical study of the Chinatowns of Amsterdam and The Hague, it also contributes to insights into multilingual Chinatowns in a field that is dominated by Chinese and English only. This helps to reveal the functioning and hierarchy of languages and the additional complexity of multiculturalism.